1996
DOI: 10.1126/science.273.5277.953
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Budding Yeast Spindle Assembly Checkpoint Without Mitotic Spindle Disruption

Abstract: The spindle assembly checkpoint keeps cells with defective spindles from initiating chromosome segregation. The protein kinase Mps1 phosphorylates the yeast protein Mad1p when this checkpoint is activated, and the overexpression of Mps1p induces modification of Mad1p and arrests wild-type yeast cells in mitosis with morphologically normal spindles. Spindle assembly checkpoint mutants overexpressing Mps1p pass through mitosis without delay and can produce viable progeny, which demonstrates that the arrest of wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
322
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(330 citation statements)
references
References 21 publications
(6 reference statements)
6
322
1
1
Order By: Relevance
“…Our finding that TTK extends at least 50 nm from the kinetochore outer surface (modeled in Fig 5) reinforces several lines of evidence showing that altering TTK kinases participate in spindle checkpoint signaling: genetic disruption of TTK homologue MPS1 results in mitotic arrest [28,29], antibodies to Xenopus MPS1 abrogates the spindle checkpoint in egg extracts and librates CENP-E, Mad1 and Mad2 from kinetochore [24]. In addition, suppression of TTK expression in U2OS cells results in defects in spindle checkpoint [18].…”
Section: A Model Of Ttk In Spindle Checkpoint Signalingsupporting
confidence: 85%
“…Our finding that TTK extends at least 50 nm from the kinetochore outer surface (modeled in Fig 5) reinforces several lines of evidence showing that altering TTK kinases participate in spindle checkpoint signaling: genetic disruption of TTK homologue MPS1 results in mitotic arrest [28,29], antibodies to Xenopus MPS1 abrogates the spindle checkpoint in egg extracts and librates CENP-E, Mad1 and Mad2 from kinetochore [24]. In addition, suppression of TTK expression in U2OS cells results in defects in spindle checkpoint [18].…”
Section: A Model Of Ttk In Spindle Checkpoint Signalingsupporting
confidence: 85%
“…Mps1p phosphorylates Mad1p in vitro and is required for the hyperphosphorylation of Mad1p upon SAC activation [Hardwick and Murray, 1995;Hardwick et al, 1996], but it has not been demonstrated that Mad1p is its direct in vivo substrate. In the absence of Mps1p, Mad1p is not hyperphosphorylated in response to SAC activation [Hardwick et al, 1996], and neither Mad1p nor Mad2p are recruited to kinetochores [Abrieu et al, 2001;Stucke et al, 2002]. However, Mps1p overexpression can arrest the cell cycle in ndc10-1 ts mutants, which lack a functional kinetochore, indicating that the role of Mps1p in SAC function goes beyond localizing checkpoint proteins to kinetochores [Fraschini et al, 2001].…”
Section: Protein Kinases and Phosphorylation In The Spindle Checkpointmentioning
confidence: 99%
“…of budding yeast Mps1p fails to activate the spindle checkpoint in the absence of Mad3p, Bub1p, Bub2p, or Bub3p [Hardwick et al, 1996], budding yeast Mps1p regulates Dbf2p, a protein involved in the mitotic exit branch of the SAC [Fesquet et al, 1999], and fission yeast mph1 acts upstream of cdc16 and dma1 (S. Kadura and S. Sazer, unpublished data).…”
Section: The Spindle Checkpoint Is a Branched Pathwaymentioning
confidence: 99%
“…Sa surexpression provoque un arrêt en métaphase. Cet arrêt néces-site la fonction des produits de chacun des gènes mad et bub [14]. Mps1 excepté, ces gènes ne sont pas essentiels chez la levure, leur délétion n'empêchant pas la multiplication des cellules.…”
Section: Le Point De Contrôle Mitotique: à Chacun Son Lotunclassified